REKAYASA PEMBUATAN MESIN STRIP BAMBU - Firdaus, Anhar; Miyono, Miyono (Kementerian Perindustrian, 2013)
Bamboo is one of non-timber forest products that has been utilized for various purposes. One of its utilizations, as building materials, is in terms of shape and strips. However, with the rapid advancement of gluing technology, bamboo can be used as a raw material for plywood core substitution as veneer. The purpose of this research is to produce a machine strips of bamboo slats with thick uniform size that can be set suit. Before introduced to the stripper machine, bamboo stems must first be cut or thinned into the desired size. The symmetrical bamboo slats are then fed into the thinning machine using a bamboo carrier U-shaped device made of iron that leads to roll clamp. At the last roll, a steel blade is in place to divide and thin the bamboo slats. The upper roll clamp serves to clamp and press the bamboo slats. Rendement the average results of the cleavage 1 (one) sized bamboo rod 8 mm thick, 1.5 cm wide and 30 cm long with a volume of 216 cm3 based on the size of the bamboo strips obtained material thickness of 1 mm by 31.5 cm3 (7 strips) or about 14, 58%,, bamboo strip thickness of 1.5 mm by 74.25 cm3 (11 strips) or about 34.375%, and a thickness of 2 mm bamboo strips as 117 cm3 (13 strips) or approximately 54.17%.Keywords: Â bamboo, strip, thinning, machines, knife, motors